Qualitative data analysis - Tajuddin, Nor Azlin (2014)
“Bengkel Penyelidikan Kualitatif dan Aplikasi NVivo” (Qualitative Research and Nvivo Application Workshop)” is designed for medical practitioners of the Department of Public Health, School of Medical Sciences, USM. Topics covered in the workshop include stages of qualitative research, data collection techniques and report writing, with a greater emphasis on data analysis.